2018
DOI: 10.1038/s41416-018-0355-8
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of the HDM2 antagonist SAR405838 combined with the MEK inhibitor pimasertib in patients with advanced solid tumours

Abstract: BackgroundThis phase I, open-label, dose-escalation study evaluated the safety, pharmacokinetics and pharmacodynamics of combination therapy with the HDM2 inhibitor SAR405838 and the MEK1/2 inhibitor pimasertib administered orally once daily (QD) or twice daily (BID) in locally advanced or metastatic solid tumours (NCT01985191).MethodsPatients with locally advanced or metastatic solid tumours with documented wild-type TP53 and RAS or RAF mutations were enroled. A 3 + 3 dose-escalation design was employed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 19 publications
(22 reference statements)
1
31
0
Order By: Relevance
“…The most frequently occurring adverse events observed were diarrhoea (81%), blood creatine phosphokinase (77%), nausea (62%) and vomiting (62%). This study indicated that the safety profile of SAR405838 combined with pimasertib was consistent with the safety profiles of both the drugs (de Weger et al, 2019).…”
Section: Sar405838supporting
confidence: 73%
“…The most frequently occurring adverse events observed were diarrhoea (81%), blood creatine phosphokinase (77%), nausea (62%) and vomiting (62%). This study indicated that the safety profile of SAR405838 combined with pimasertib was consistent with the safety profiles of both the drugs (de Weger et al, 2019).…”
Section: Sar405838supporting
confidence: 73%
“…The components of this pathway play a very important role in the genesis of cancer, which has been reported many times before [183,184,185]. p53 and the MAPK components are the most frequently mutated tumor suppressor and oncogene pathways in human cancers [81]. For this reason, there is a great potential in simultaneous targeting of these two pathways to provide useful therapeutic approaches.…”
Section: Drug Combinations For the Supporting Of Anti-cancer Activmentioning
confidence: 99%
“…Development of small molecules disrupting the MDM2–P53 interactions has been highly pursued from academia to industry in recent years 5 , 9 , 10 , 11 , 12 , 13 , 14 . Some of these inhibitors including DS-3032 (also known as Milademetan, DS-3032b) 15 , 16 , NVP-CGM097 17 , 18 , 19 , SAR405838 20 , 21 , 22 , RG7112 23 , 24 , MK-8242 25 , 26 , RG7388 27 and AMG 232 28 , 29 , 30 ( Fig. 2 ) are under clinical evaluation for anticancer treatment.…”
Section: Introductionmentioning
confidence: 99%